Klotho and The Kidney - Sourabh Sharma; Neha Sharma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2026)
Klotho has emerged as one of the most important renoprotective proteins linking kidney function with systemic metabolic, endocrine, and cardiovascular health. Predominantly expressed in the renal tubules, Klotho regulates phosphate homeostasis through the fibroblast growth factor-23 (FGF23) pathway while exerting pleiotropic effects on oxidative stress, inflammation, fibrosis, mitochondrial function, and cellular senescence. Declining Klotho expression is a hallmark of chronic kidney disease (CKD) and contributes to mineral bone disorder, vascular calcification, accelerated ageing, and progressive renal dysfunction. Beyond serving as a biomarker of kidney health, Klotho represents a promising therapeutic target capable of enhancing renal resilience and slowing disease progression. Lifestyle interventions, particularly regular exercise, together with emerging pharmacological strategies, may preserve endogenous Klotho expression and contribute to nephroprotection. As nephrology evolves toward a cardiorenal-metabolic paradigm, Klotho provides a unifying biological framework connecting the kidney with multiple organ systems. Future research into Klothobased diagnostics and therapeutics may transform the prevention and management of CKD and its systemic complications. Keywords: Ageing, Cardiorenal syndrome, Chronic kidney disease, Exercise, Fibroblast growth factor 23, Mineral metabolism, Vascular calcification.